Independent Character Building of Special Needs Children in Special Elementary School - Rico Yuda Permana Putra; Suyatno Suyatno (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2021)
This study aims to describe the implementation of instilling independent character in SLB N 1 of Yogyakarta. The used research design was qualitative research using a case study. Data collection was conducted by interview, observation, and documentation. The collected data was analyzed using interactive-inductive analysis technique encompassed data reduction, data representation, and conclusion. The research result showed that (1) the indicator of independent character in SLB N 1 of Yogyakarta showed by preparing the need for studying, having self-confidence, individually finishing the assignments, being dare to express an opinion, group cooperation, reading and writing correctly also adequately., doing the calculation task independently. (2) Instilling independent character addressing special-needs students was carried out through learning activities, direct teaching, spontaneous activity, exemplary, and daily habituation. This finding can be used by stakeholders and inclusive educational practitioners to organize and conduct independent character building for special-needs students at school.